2007
DOI: 10.1038/sj.onc.1210359
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent activation of the hedgehog pathway in glioma progenitor cells

Abstract: The hedgehog (Hh) signaling pathway regulates progenitor cells during embryogenesis and tumorigenesis in multiple organ systems. We have investigated the activity of this pathway in adult gliomas, and demonstrate that the Hh pathway is operational and activated within grade II and III gliomas, but not grade IV de novo glioblastoma multiforme. Furthermore, our studies reveal that pathway activity and responsiveness is confined to progenitor cells within these tumors. Additionally, we demonstrate that Hh signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(142 citation statements)
references
References 31 publications
6
129
0
7
Order By: Relevance
“…Because of the established role for Hh signaling both in normal neural precursor cells (9,15,17,18) and in other brain tumors, such as medulloblastoma (19)(20)(21)(22), we postulated that the Hh pathway might play a role in transformation of this ventral PPC population. To test the functional and possibly oncogenic role of the Hh pathway in ventral pontine Olig2 + precursor cells, we used a genetic mouse model in which the Hh pathway is specifically up-regulated in Olig2 + cells.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the established role for Hh signaling both in normal neural precursor cells (9,15,17,18) and in other brain tumors, such as medulloblastoma (19)(20)(21)(22), we postulated that the Hh pathway might play a role in transformation of this ventral PPC population. To test the functional and possibly oncogenic role of the Hh pathway in ventral pontine Olig2 + precursor cells, we used a genetic mouse model in which the Hh pathway is specifically up-regulated in Olig2 + cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Gli activity correlates with tumor grade in a genetically engineered mouse model (Becher et al, 2008). Several groups have investigated the role of Hedgehog-Gli signaling in GSCs and found that this signaling pathway regulates self-renewal and tumorigenic potential of GSCs (Clement et al, 2007;Ehtesham et al, 2007;Bar et al, 2007;Xu et al, 2008). Treatment of GSCs with the Hedgehog inhibitor cyclopamine or Gli RNA interference suppresses self-renewal and proliferation while increases apoptotic cell death.…”
Section: Hedgehog-gli Signalingmentioning
confidence: 99%
“…Relevant benefits of primary orthotopic glioma xenografts include infiltrative growth that typifies diffuse gliomas and the retention of genetic alterations and important signaling mechanisms that can be exceedingly difficult to maintain in cultured glioma cells. For example, isocitrate dehydrogenase mutations and Sonic hedgehog ligand production can be maintained in primary orthotopic xenografts 15,16 but only rarely in cultured glioma cells 14,[17][18][19] . It is important to consider significant disadvantages of primary orthotopic xenografts, however, depending upon experimental needs.…”
Section: Discussionmentioning
confidence: 99%